2000
DOI: 10.1115/1.483211
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Brush Pocket Damper Seals for Turbomachinery

Abstract: Pocket damper seals perform a dual function: both sealing the pressurized gas around a rotating shaft and providing large amounts of vibration damping. The annular cavity between the labyrinth seal teeth is subdivided into separate annular cavities around the circumference of the rotor by partitioning walls. Also, the upstream and downstream teeth have different radial clearances to the rotor. These seals have been shown to provide a remarkable amount of direct damping to attenuate vibration in turbomachinery,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…These three seals had the same diameter, overall length, and radial clearance. The two lowest-leaking seals are hybrid designs using brush elements and wire mesh elements contacting the journal [40].…”
Section: Impedance Measurements Of Pocket Damper Seal Force Coefficiementioning
confidence: 99%
“…These three seals had the same diameter, overall length, and radial clearance. The two lowest-leaking seals are hybrid designs using brush elements and wire mesh elements contacting the journal [40].…”
Section: Impedance Measurements Of Pocket Damper Seal Force Coefficiementioning
confidence: 99%
“…Their studies confirmed that the use of a non-Darican approach gave better agreement to experimental results. Laos et al [19] described a recently developed hybrid brush pocket damper seal that combines high damping with low leakage. The main objective of their experiments was to measure the damping and leakage of brush hybrid seals and six-bladed labyrinth seals of the same working dimension for comparison.…”
Section: Introductionmentioning
confidence: 99%